Impact of climate change on the apple economy of Himachal Pradesh: A case study of Kotgarh village - Singh, Inder Jeet (Видавництво Львівської політехніки, 2013)
In Himachal Pradesh agro-climatic conditions are suitable for the cultivation of variety of fruit crops. The development of these crops has greatly fulfilled the needs and objectives of socio-economic growth in the state. Among various fruit crops grown in the state apple dominate in area as well as production. Himachal Pradesh is the second largest producer of apple in India. But due to environmental change some areas are experiencing decline in the productivity of apple in the state. The present study is an attempt to analyze the changes in the growth of apple orchards in terms of space and time in response to changing environment. The study will be based on primary as well as secondary data. One time Himachal Pradesh was known for best quality apple in the country but now in many parts of the state apple has become uneconomical, nonviable, less profitable and even unproductive. Over the years, fruit growers in the study area have observed significant variations in climate. This awareness of climate change is based mainly on the associated impacts on the apple crop especially on blossoming, fruit setting, yield and increased incidences of pests and diseases. Over all the climate is described as being much warmer and people perceive a definite reduction in snowfall over time. Not only has the actual amount of snowfall decreased but changes in timing of snowfall have also been noticed. Snowfall in December and January has become rare and the period of snowfall now extends through the months of February-March. As a result to maintain an apple orchard has been become an uphill task. New trees simply don’t survive and older ones are dying fast and the farmers have switched over to other fruits and vegetables.
Keywords: climate change; apple; economy; snowfall; temperature; rainfall